Performa Profesi Advokat sebagai Officium Nobile menurut Pandangan Netizen (Studi Kasus Sdr. RAN) - Baren Sipayung; Julius Ibrani; Henri Wilson Lubis (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This article reviews the legal problems experienced by RAN Advocates, a prominent legal practitioner in Indonesia, and their impact on the image of advocacy in the country. Using data from various sources such as news reports and court decisions, this article examines issues related to ethical violations, conflicts of interest, and professional standards. Analysis shows that the RAN case has affected its reputation and the image of the advocacy profession as a whole. Although advocate organizations have made efforts to deal with cases like this, challenges remain, especially when involving influential advocates. This article emphasizes the importance of stronger internal controls and a more robust legal system in maintaining quality and public trust in the advocacy profession.